Penentuan Kadar NPK (Nitrogen, Fosfor dan Kalium) dari Pelepah Aren (Arenga Pinnata M.) - Hesti; Rahmanpiu; La Rudi (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
Research has been carried out to determine the levels of NPK (Nitrogen, Phosphorus and Potassium) in the palm fronds (Arenga pinnata M.). Palm fronds can be used as a growing medium. One indicator of a material that can be used as a growing medium is the availability of nutrients. So the purpose of this study was to determine the feasibility of the palm midrib (Arenga pinnata M.) to be used as a growing medium. The method used to determine the levels of NPK (Nitrogen, Phosphorus and Potassium) used a different method. Determination of nitrogen content was determined using the Kjeldahl method, phosphorus using the UV-Vis Spectrophotometer method and potassium using the Atomic Absorption Spectrophotometer method. Based on the results of research conducted, on the palm fronds, the results obtained with nitrogen levels of 0.171%, Phosphorus of 1.826% and Potassium of 0.0022%. From the results of these studies that meet the requirements as a planting medium is Phosphorus so that the palm fronds can be recommended to be used as a planting medium.